2020
DOI: 10.3390/pr8030332
|View full text |Cite
|
Sign up to set email alerts
|

Dual Solutions and Stability Analysis of Magnetized Hybrid Nanofluid with Joule Heating and Multiple Slip Conditions

Abstract: This paper investigates the steady, two dimensional, and magnetohydrodynamic flow of copper and alumina/water hybrid nanofluid on a permeable exponentially shrinking surface in the presence of Joule heating, velocity slip, and thermal slip parameters. Adopting the model of Tiwari and Das, the mathematical formulation of governing partial differential equations was constructed, which was then transformed into the equivalent system of non-linear ordinary differential equations by employing exponential similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 55 publications
3
61
0
Order By: Relevance
“…The same state of heat transfer rate was obtained by Lund et al [19,20] during the examination of a hybrid nanofluid. Yan et al [21] also found similar results when they analyzed a hybrid nanofluid over the exponential surface with joule heating effects. Further, it is stated that "the skin friction coefficient, f (0), enhances for the first solution when the suction S and magnetic M parameters are increased, while f (0) reduces for the higher effect of the velocity slip factor, δ".…”
Section: Introductionmentioning
confidence: 59%
“…The same state of heat transfer rate was obtained by Lund et al [19,20] during the examination of a hybrid nanofluid. Yan et al [21] also found similar results when they analyzed a hybrid nanofluid over the exponential surface with joule heating effects. Further, it is stated that "the skin friction coefficient, f (0), enhances for the first solution when the suction S and magnetic M parameters are increased, while f (0) reduces for the higher effect of the velocity slip factor, δ".…”
Section: Introductionmentioning
confidence: 59%
“…Referencing the work reported by Merkin [55], Weidman et al [56], Waini et al [16] and Yan et al [38], the dimensionless time-dependent variable transformation for Equations (11) and ( 12) is…”
Section: Flow Stabilitymentioning
confidence: 96%
“…where γ is an unidentified eigenvalue, while F(η) and G(η) are small relative to f 0 (η) and θ 0 (η), correspondingly (Weidman et al [56], Waini et al [16], Yan et al [38]). Substituting Equation ( 17) into Equations ( 14)-( 16) and setting the value of τ to zero, the initial decay or growth of disturbance in Equation ( 17) can be identified and the subsequent linearized equations are attained…”
Section: Flow Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ismail et al 20 considered a moving flat plate in a parallel stream to analyze the heat transfer with constant heat flux. The characteristics of an axisymmetric mixed convection flow of a copper nanofluid and slip effects were determined by Soomro et al 21 Some latest studies about dual solutions are found in References 22‐25 …”
Section: Introductionmentioning
confidence: 99%